Assessment of Lumiaggregometry for Research and Clinical Laboratories - White, Melanie McCabe; Foust, John T; Mauer, Alvin M; Robertson, James T; Jennings, Lisa K (Thrombosis and Haemostasis, 1992)
Platelet aggregometry is often used to help diagnose storage pool disease (SPD-reduced amounts of granule nucleotides) and release defects (abnormal release of granule nucleotides). The general assumption that normal aggregation patterns are sufficient to rule out the diagnosis of one of these disorders has been invalidated by the recent publication of two papers describing patients with clinical bleeding, prolonged bleeding times and normal aggregation patterns in spite of defective release. The lumiaggregometer provides a tool for measuring platelet release and aggregation simultaneously. This paper presents a standardized, reproducible method for the use of the lumiaggregometer based on a “standard curve”. Data obtained during the development of the procedure are presented including normal ranges of release at different concentrations of agonists, release measured in intrinsic disorders as well as in patients on aspirin, and values for release relative to varying platelet counts. A monoclonal antibody (anti-p24/CD9; MAb7) which activates platelets similarly to thrombin and may be a useful reagent for distinguishing SPD and release defects is also introduced.